JORNAL O PANTANEIRO: MEMÓRIA, HISTÓRIA E CULTURA - LISE ROSSI JONES LIMA (2023)
In recent years, there has been a significant increase in academic research that analyzes the trajectory of periodicals published in Brazil. There are a number of studies focused on newspapers and magazines published in Brazilian capitals. However, there are fewer investigations on newspapers produced in the interior of the country. Therefore, the present research has as its object the newspaper O Pantaneiro, published in the municipality of Aquidauana, in Mato Grosso do Sul. The period of the investigation is 1965, the year the periodical was launched. The final time frame is 1978, seeking to contemplate the period of creation of the south-mato-grossense state, as well as the first years of the administration of the current owner of O Pantaneiro. The dissertation aims to investigate the trajectory of the newspaper and its characteristics, as well as the performance of its leaders and the productions of the first female voices that collaborate with the periodical. Furthermore, it is intended to consider the local means of communication and moments in the development of the press. To develop the study, an interdisciplinary theoretical posture is adopted, provided by Cultural Studies and by the articulation of concepts from the areas of Communication and History. Regarding the methodology, it was essential to use bibliographical research and to conduct documentary research in the newspaper's collection. As a result of the research process, a dissertation in four chapters is presented.